Pseudoachondroplasia and painful sequelae. (14th July 2015) - Gamble, Candace; Nguyen, Joanne; Hashmi, S. Shahrukh; Hecht, Jacqueline T.
<x xml:space="preserve">Abstract</x> Pseudoachondroplasia (PSACH) is a well‐described autosomal dominant short limb dwarfing condition caused by mutations in the cartilage oligomeric matrix protein gene (COMP). The most debilitating complication of the disorder is joint pain starting in childhood, the extent and severity of which is poorly defined. The aim of this study was to fully assess the pain and identify additional clinical complications affecting those with PSACH. An online survey was distributed to individuals with PSACH. Of the 77 surveys analyzed, 83% reported chronic pain starting as early as the newborn period. Pain was most frequently reported in weight bearing joints including the knees, hips, and back, and significantly interfered with their overall quality of life. For pain relief, patients with PSACH used a wide variety of treatments. However, patients reported only a 60% resolution of pain with their current treatments. An increase in other comorbidities was not found, specifically osteoporosis was not increased. This study documents for the first time that pain is the most common presenting symptom in PSACH and is often overlooked until short stature becomes obvious. The recognition of chronic pain as one of the earliest manifestations of PSACH is important to allow for prompt diagnosis. © 2015 Wiley Periodicals, Inc.